DIGITAL HEALTH TECHNOLOGIES AND THE NURSE–PATIENT RELATIONSHIP: INSIGHTS FROM SOUTH AFRICAN HOSPITALS - Faeda Mohsam (PEOPLE: International Journal of Social Sciences, 2026)
This study explores how technology shapes the nurse-patient relationship, enhancing efficiency, responsiveness, and monitoring while posing risks to personal interaction. Guided by Normalization Process Theory (NPT), a qualitative interpretive design was used to examine nurses’ experiences with digital health technologies (DHTs) in two Western Cape hospitals. Using purposive sampling, 28 participants provided in-depth insights analysed thematically. Findings show that DHTs improved efficiency, accuracy, and patient monitoring but also reduced face-to-face interaction, increased administrative tasks, and required ongoing training. Administrators valued DHTs’ strategic benefits yet stressed the need to address relational and practical challenges. Overall, the study reveals the dual impact of DHTs - enhancing efficiency while challenging relational care - and offers insights into balancing digital innovation with patient-centered practice in South African hospitals during crises, but offers novel insight into its importance. These findings highlight the strategic value of developing communication skills.